CircRNA Expression Profiles and the Potential Role of CircZFP644 in Mice With Severe Acute Pancreatitis via Sponging miR-21-3p - Yang, Yi; Ren, Jiandong; Huang, Qilin; Wu, Jun; Yuan, Xiaohui; Jiang, Wen; Wen, Yi; Tang, Lijun; Sun, Hongyu (Frontiers in Genetics, 2020)
Severe acute pancreatitis (SAP) is the most serious type of pancreatitis with high morbidity and mortality. The underlying mechanism behind SAP pathogenesis is complex and remains elusive. Circular RNAs (circRNAs) are emerging as vital regulators of gene expression in various diseases by sponging microRNAs (miRNAs). However, the roles of circRNAs in in the pathophysiology of SAP remain unknown. In the present study, next-generation RNA sequencing was utilized to identify circRNA transcripts in the pancreatic tissues from three SAP mice and three matched normal tissues. The differentially expressed circRNAs were confirmed by real-time PCR and the biological functions of their interaction miRNAs and mRNAs were analyzed. Our results discovered that 56 circRNAs were differently expressed in SAP compared with normal control. Six differentially expressed circRNAs were confirmed with the sequencing data. Importantly, we characterized a significantly downregulated circRNA derived from the ZFP664 gene in SAP. CircZFP644 was found to have a tendency of negative correlation with miR-21-3p, and a perfect match binding sequence to miR-21-3p. In conclusion, CircZFP644 may play an important role in the pathogenesis of SAP through sponging miR-21-3p. Our findings may provide novel insights for pathophysiological mechanism of SAP and offer novel targets for SAP.